Language Screening for Infants and Toddlers: A Literature Review of Four Commercially Available Tools. (November 2016) - Larson, Anne L.
Children from low-income environments are at increased risk of developing language delays which can negatively affect later academic and social outcomes. As children age, deficits between children with language delays and their typically developing peers continue to widen. In order to prevent future disabilities, efficient early language screening tools are needed to identify infants and toddlers who are at risk of language delay as the first step towards providing early intervention. The purpose of this review was to identify commercially available language screening tools for use with children under three years of age. The psychometric properties of each tool are described—including a specific focus on technical adequacy of the measures for use with diverse families. There are currently four tools available for use with infants and toddlers. The strengths and limitations of each tool are described, as well as the feasibility of using these tools in diverse populations.